2003
DOI: 10.1002/ijc.11127
|View full text |Cite
|
Sign up to set email alerts
|

Increased protein expression of DNA methyltransferase (DNMT) 1 is significantly correlated with the malignant potential and poor prognosis of human hepatocellular carcinomas

Abstract: Alteration of DNA methylation is one of the most consistent epigenetic changes in human cancers. DNA methyltransferase (DNMT) 1 is a major enzyme involved in establishing genomic methylation patterns. Most of the studies concerning DNMT1 expression in human cancers have been performed only at the mRNA level. To directly examine DNMT1 protein expression levels during human hepatocarcinogenesis, 16 histologically normal liver tissues, 51 noncancerous liver tissues exhibiting chronic hepatitis or cirrhosis, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
166
4
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(181 citation statements)
references
References 33 publications
10
166
4
1
Order By: Relevance
“…Increased DNMT1 expression indicates worse outcomes in several types of cancers, such as gastric cancer, hepatocellular carcinomas and pancreatic ductal adenocarcinoma [10,26,33]. In contrast, our analysis showed no difference in disease outcome when comparing patients with no/weak and moderate/strong expression of three DNMTs, so DNMTs are not predictive markers for medulloblastoma survival.…”
Section: Discussioncontrasting
confidence: 71%
“…Increased DNMT1 expression indicates worse outcomes in several types of cancers, such as gastric cancer, hepatocellular carcinomas and pancreatic ductal adenocarcinoma [10,26,33]. In contrast, our analysis showed no difference in disease outcome when comparing patients with no/weak and moderate/strong expression of three DNMTs, so DNMTs are not predictive markers for medulloblastoma survival.…”
Section: Discussioncontrasting
confidence: 71%
“…DNMT1 plays an important role in the maintenance of DNA methylation status. Overexpression of DNMT1 has been detected in many cancers, such as gastric cancer (Etoh et al, 2004), hepatic cancer (Saito et al, 2003), endometrial cancer (Liao et al, 2008), prostate cancer (Morey Kinney et al, 2008) and pancreatic cancer (Peng et al, 2005), suggesting that DNMT1 overexpression has some significance during tumor carcinogenesis. Previously, our data demonstrated that the expression of DNMT1 was significantly higher both at the protein and mRNA levels in most ESCC tissues compared to paired noncancerous tissues .…”
Section: Discussionmentioning
confidence: 99%
“…Over-expression of DNMT3B has been observed in some cancer types, and it contributes to the generation of aberrant methylation in cancer [19][20][21][22][23][24][25][26]. As we previously reported, the DNMT3B contains a C-T transition polymorphism (C46359T) at a novel alternative promoter region, -149 base pairs from the transcription start site, which in in vitro assays confers a 30% increase in the promoter activity of DNMT3B [13].…”
Section: Discussionmentioning
confidence: 99%